Shiva depicted in a dance posture - Temples of India Project Team (Jio Institute, 2024)
Shiva is depicted in a dance posture. Standing in the urdhvajanu (upraised knee) pose, Shiva is depicted with multiple arms, each embodying cosmic significance. In his upper hands, he holds a multi-hooded sarpa (serpent) and a damru (drum), symbolizing creation and destruction in the cosmic dance of life. His right and left middle arms are damaged, but some are intact. His lower left hand forms the gajahasta (elephant trunk) gesture. In the lower right corner, a drummer is depicted, accompanying Shiva’s celestial dance with the beats of a drum. Meanwhile, at the opposite corner, Shiva’s mount, Nandi, is depicted in a seated posture.